Answer: Second answer choice.
==========================================================
Step-by-step explanation:
We have a 1x3 matrix multiplied with a 3x3 matrix. This is a valid operation since the number of columns in the first matrix matches with the number of rows in the second matrix.
The resulting answer matrix will be 1x3 as it takes the number of rows of matrix A and the number of columns from matrix B, helping forming the answer matrix C.
The answer matrix looks like
where x, y and z are placeholders for actual numbers.
To get the value of x, we apply the dot product of the left matrix with the first column of the right matrix
x = (-1)(3)+(2)(2)+4(0) = -3+4+0 = 1
We'll do a similar set of steps to find y
Apply the dot product on the second column this time
y = (-1)(6)+2(4)+4(6) = -6+8+24 = 26
and the third column as well
z = (-1)(1)+2(0)+4(2) = -1+0+8 = 7
Since x = 1, y = 26 and z = 7, we can say
becomes